Activation Energy in Photochemical and Thermally Driven Reactions: Mechanistic Insights, Kinetic Modelling and Photocatalytic Applications - Pushpa Mehdoo; Meena Bandhan; S. Ravichandran (International Journal of Photochemistry and Photochemical Research, 2026)
Chemical reactions constitute fundamental processes in which reactants are transformed into products through the breaking and formation of chemical bonds. In photochemical systems, these transformations are initiated or influenced by the absorption of light, making energy transfer mechanisms particularly significant. A key parameter governing reaction kinetics is activation energy, defined as the minimum energy required for reactant molecules to undergo a successful transformation. This article focuses on the role of activation energy within the context of photochemical and photophysical processes. It discusses various types of chemical reactions with particular emphasis on light-induced reactions, where photons act as the primary energy source to overcome activation barriers. The influence of external factors such as light intensity, wavelength, temperature, and reactant concentration on activation energy and reaction rates is critically examined. Furthermore, the role of photocatalysts is highlighted, as they facilitate reactions by providing alternative pathways with reduced activation energy under light irradiation, without being consumed in the process. Such mechanisms are central to advancements in areas including solar energy conversion, environmental remediation, and photo-driven synthesis. Understanding activation energy in photochemical systems enables reaction conditions, thereby enhancing efficiency and sustainability in diverse applications ranging from green chemistry to biological photo processes.
Keywords: Photochemical processes; excited-state energy barriers; light-induced kinetics; molecular collision dynamics; photoactivation energy; photocatalysis; photochemical reaction mechanisms; photoenzymatic catalysis; photoreaction kinetics; temperature effects on photoreactions